Predation of the diving beetle, Eretes sticticus (Coleoptera: Dytiscidae) on mosquito larvae, Culex pipiens L. (Diptera: Culicidae) - Younes, A. A. (2008)
Mosquitoes are probably the best known group of insects because of their importance as nuisance pests and vectors of animal and human diseases. They are widely distributed through the world and occur in a variety of habitats (Yan and Zhong, 2005). Larvae of mosquitoes have been traditionally controlled with synthetic pesticides. This type of control can be hazardous to human, result in pesticide resistance in mosquitoes, damaging fauna and flora, contaminat- . ing air, water and soil, and being expensive (Hemingway et al., 2004).
Includes reference.
1
Keywords: Predatory aquatic animals; Mosquitoes -- Larvae .; Dytiscidae; Culex pipiens -- Life cycles -- Juvenile literature